2006
DOI: 10.1002/app.23263
|View full text |Cite
|
Sign up to set email alerts
|

Soybean oil based resin: A new tool for improved immobilization of α‐amylase

Abstract: Acrylated epoxidized soybean resin has been utilized to immobilize the ␣-amylase via UV-curing technique. Among the numerous methods that exist for enzyme immobilization, entrapment and covalent binding are the focus of this study. The properties of immobilized enzyme were investigated and compared with those of the free enzyme. Upon immobilization by the two methods, the catalytic properties of the enzyme were not considerably changed as compared with that of nonimmobilized form; only the pH profile was broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 13 publications
1
22
0
Order By: Relevance
“…It was observed that the 35th use, immobilized sample retained 73% of its initial activity. In our previous study, it was found that, the reuse capabilities of a-amylase were in the range of 74-88% when immobilized on epoxidized soybean based support [18].…”
Section: Effect Of Storage and Reusability On Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…It was observed that the 35th use, immobilized sample retained 73% of its initial activity. In our previous study, it was found that, the reuse capabilities of a-amylase were in the range of 74-88% when immobilized on epoxidized soybean based support [18].…”
Section: Effect Of Storage and Reusability On Activitymentioning
confidence: 99%
“…Because it has very low water absorption capacity and negligible shrinkage behavior it can be assumed as very good candidate for a rigid enzyme carrier [18].…”
Section: Characterization Of Polymeric Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the 20th cycle, the residual activity retained was approximately 57.62%. Kahraman et al studied the reuse capability of α‐amylase and found that it was in the range of 74–88% when immobilized on UV curable support after 50 cycles. In another study on α‐amylase immobilized calcium carbonate nanoparticles, it was demonstrated that the immobilized enzyme could reuse 25 times while retaining 18.2% of its activity.…”
Section: Resultsmentioning
confidence: 99%
“…The three bands at 1247, 1196, and 1169 cm -1 signified fatty acid methyl esters, as previously noted in linseed oil-based epoxidized methyl ester (Martini et al 2009). In the AEHO spectrum, the peak at 3400 to 3800 cm -1 (peak d) was attributed to the hydroxyl groups formed by the acrylic acid reaction and cleavage of the epoxide groups (La Scala et al 2004;Kahraman et al 2006). Furthermore, the peak visible at 1630 cm -1 (peak e) represented stretching vibrations of the C=C groups in acrylic acid.…”
Section: Ftir Spectroscopymentioning
confidence: 99%